Efficacy of Intramuscular Platelet Rich Plasma Versus Oral Antihistamine In Chronic Urticaria - Naseemullah, Abdul Qayum Khan, Farooq Azam Khan, Shahzad Rashid Awan, Mehran Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Chronic urticaria is defined as a pruritic skin disorder that persists daily or about daily for ˃6 weeks. Chronic urticaria is a common problem in Pakistan. The common treatment method is oral histamine. Currently the important treatment method used is autologous serum therapy. The objective of this study was to determine the efficacy of intramuscular platelet rich plasma versus oral antihistamine in the treatment of chronic urticaria Methodology: This study was randomized controlled clinical trial carried out at the Dermatology Department, Qazi Hussain Ahmad Complex Nowshera and alshifa clinic and skin aesthetic, Nowshera from May 2020 to May 2021. 100 patients were included in this research work. They were randomly divided into two groups of 50 patients each. One group was given autologous serum while the other was given antihistamine. The autologous serum group patients were treated by giving 9 intramuscular injection of autologous serum while the antihistamine group patients were treated with oral antihistamine on routine basis. UAS-7 (Urticaria Activity score-7) was used for measuring the effectiveness of both the treatment methods. Results: At baseline in autologous serum group, the Urticaria activity score was 36.1 (±6.7) while in antihistamine group it was 35.2 (±5.4) respectively. At baseline Urticaria activity score was non-significant (p=0.85). At 4th week the mean Urticaria activity score in autologous serum group and antihistamine group was 18.3(±3.6) and 30.2.1 (±5.1) (p=0.01). At 9th week in autologous serum group, the Urticaria activity score was 11.3 (±6.3) while in antihistamine group it was 22.6 (±4.9). (p=0.04) At 12th week the mean Urticaria activity score in autologous serum group and antihistamine group was 7.1(±5.4) and 20.4 (±7.3) respectively (p=0.01). Keywords: Chronic Urticaria; Intramuscular platelet rich plasma; Oral antihistamine.